Layanan Konseling Kelompok dengan Menggunakan Pendekatan Cognitive Behavioral untuk Membentuk Internal Locus of Control - Sujadi, Eko; Ayumi, Rinda Tri; Indra, Syaiful; Sumarto, Sumarto; Rahima MRA, Raja (Jurnal Fokus Konseling, 2018)
Internal locus of Control needs to be owned by every individual, including students. Individuals who oriented in internal locus of control will believe that they have a major role to influence events related to their lives. A strategy that can be used to forming internal locus of control is group counseling by using cognitive behavioral approach. The purpose of this research was to reveal the effectiveness of group counseling by using cognitive behavioral approach in forming internal locus of control. This research was experimental research with pretest and post-test control group design. The sample had been chosen by using purposive sampling. The instrument that had been used was Internal Rottersâ inventory -External Locus of Control (I-E Scale). Data were analyzed by using Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Samples. The findings of this research were: (1) there was a difference of locus of control in experimental group students before and after being treated; (2) there was a difference of locus of control in control group before and after being treated; and (3) there was a difference in studentsâ locus of control in experiment and control group.Keywords:Â  group counseling, cognitive behavioral, internal locus of control.